Mapping the geography of choirs in Sweden - Göransson, Per (Approaching religion, 2022)
The geography of choirs has seldom received attention in human geography and even less so in a Swedish context. This article analyses the geography of choirs in Sweden by focusing on choir members in the Church of Sweden. Sweden offers an interesting case of choral geography because of (1) the Church of Sweden’s geographical presence, (2) the number of choir members, and (3) the role of religion in contemporary Swedish society. An intimation of the contemporary significance is that the Church of Sweden has 78,170 choir members in 2020 and is active in every municipality. The data consist of the Church of Sweden membership and choir members visualized in turn on maps. The qualitative analyses of the quantitative data reveal that there seem to be few youth-choir members in Sweden. There seem to be many children choir members in the larger cities but fewer in rural areas. The northern part of Sweden seems to have generally lower levels of choir members but higher membership in the Church of Sweden. Another finding is that high membership in the church does not necessarily mean a high number of choir memberships. For further studies, quantitative engagement with more datasets together with an engagement with post-secular theories is suggested.